The Growing Scientific Attitudes and Worship to Science for Students - Hirma Meuthia (International Journal of Educational Dynamics, 2019)
This study presents a literature review on growing scientific attitudes and literacy towards science for students. Natural science is a product, process, and ends with an attitude that is a scientific attitude. Scientific attitudes are developed through scientific literacy activities or processes in learning when conducting discussions, experiments, simulations, and project activities at the field. Although in the world of education, we have encountered many models that carry out the activities described above in developing students' scientific attitudes. Some of them are inquiry, discovery learning, problem-based learning, project-based learning, and contextual learning. The learning model improves the scientific attitude in learning. However, there are some obstacles in its efforts to foster the scientific attitude of students, one of the problems is that educators lack the relevant pedagogical skills needed in learning in an atmosphere of inquiry. Another disadvantage is that the background of teachers' understanding of scientific literacy content is still poor. This research was conducted to see the factors that influence the scientific attitude of students. Literature research results show that the scientific attitude of students will be positive, if the ability of educators in scientific learning and literacy of science is mastered by the teacher.